Is short-term exposure to PM2.5 relevant to childhood Kawasaki disease? - Oh, Jongmin; Lee, Ji Hyen; Kim, Eunji; Kim, Soontae; Kim, Hae Soon; Ha, Eunhee (International Journal of Environmental Research and Public Health, 2021)
Background: Kawasaki disease (KD) is an acute febrile vascular disease of unknown cause that affects the whole body. KD typically occurs in infants under the age of five and is found mainly in East Asian countries. Few studies have reported on the relationship between the pollutant PM2.5 and KD, and the evidence remains irrelevant or insufficient. Objectives: We investigated the relationship between short-term exposure to PM2.5 and KD hospitalizations using data from Ewha Womans University Mokdong Hospital, 2006 to 2016. Methods: We obtained data from the hospital EMR (electronic medical records) system. We evaluated the relationship between short-term exposure to PM2.5 and KD hospitalizations using a case-crossover design. We considered exposures to PM2.5 two weeks before the date of KD hospitalization. We analyzed the data using a conditional logistic regression adjusted for temperature and humidity. The effect size was calculated as a 10 µg/m3 increase in PM2.5 concentration. We performed a subgroup analysis by sex, season, age group, and region. In the two-pollutants model, we adjusted SO2, NO2, CO, and O3, but the effect size did not change. Results: A total of 771 KD cases were included in this study. We did not find any statistically significant relationship between PM2.5 and children’s KD hospitalization (two-day moving average: odds ratio (OR) = 1.01, 95% confidence intervals (CI) = 0.95, 1.06; seven-day moving average: OR = 0.98, CI = 0.91, 1.06; 14-day moving average: OR = 0.93, CI = 0.82, 1.05). A subgroup analysis and two pollutant analysis also found no significant results. Conclusion: We did not find a statistically significant relationship between PM2.5 and children’s KD hospitalizations. More research is needed to clarify the association between air pollution, including PM2.5, and KD.
Keywords: Air Pollutants; Air Pollution; Child; Environmental Exposure; Far East; Female; Humans; Infant; Mucocutaneous Lymph Node Syndrome; Particulate Matter; Case-crossover design; Children; Kawasaki disease; PM2.5